Generating Skin Distribution Map of Face Images - Setiawan Hadi; Adang Suwandi A.; Iping Supriana S.; Farid Wazdi (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2006)
Skin pixel visualization in a digital image has been considered as an important clue that can be used in many advanced computer vision applications. This paper describes the steps to present skin distribution by mapping pixel intensities of face-contain images into a two dimensional representation. The face images are originated from three face database groups, those are FERET database, SI synthesized face generator, and Indonesian face database called DWI. Experiment has been performed to visualize the SDM in three chromatic color spaces.Keywords: SDM, Skin, Face, Image, Skin Distribution Map.